Global gene expression analysis of amniotic fluid cell-free RNA from recipient twins with twin-twin transfusion syndrome - Hui, Lisa (2013)
OBJECTIVE: To understand the biological pathways involved in twin-twin transfusion syndrome (TTTS) by performing global gene expression analysis of amniotic fluid (AF) cell-free RNA. METHODS: Prospective whole transcriptome microarray study analyzing cell-free RNA in AF from TTTS recipient twins and singleton controls. Significantly differentially-regulated genes in TTTS cases (N= 8) vs. matched controls (N = 8) were identified and pathways analyses performed. Significant gene expression differences between Stage II TTTS recipients (N = 5) and Stage III TTTS recipients with abnormal Doppler measurements (N = 5) were also analysed. RESULTS: Analysis of paired data from TTTS cases and controls revealed differential expression of 801 genes, which were significantly enriched for neurological disease and cardiovascular system pathways. We also identified cardiovascular genes and pathways associated with the presence of critically abnormal Doppler measurements in Stage III TTTS recipients. CONCLUSIONS: This study provides the first transcriptome-wide data on the impact of TTTS on fetal development. Our results show that gene expression involving neurological and cardiovascular pathways are altered in recipient fetuses prior to surgical treatment. This has relevance for the origins of long-term complications seen in survivors and for the development of future fetal biomarkers.